2019
DOI: 10.1111/ajt.15196
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of interferon regulatory factor 4 in T cells induces “memory” of transplant tolerance that is irreversible by immune checkpoint blockade

Abstract: Achieving transplant tolerance remains the ultimate goal in the field of organ transplantation. We demonstrated previously that ablation of the transcription factor interferon regulatory factor 4 (IRF4) in T cells induced heart transplant acceptance by driving allogeneic CD4+ T cell dysfunction. Herein, we showed that heart‐transplanted mice with T cell‐specific IRF4 deletion were tolerant to donor‐specific antigens and accepted the subsequently transplanted donor‐type but not third‐party skin allografts. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Another setting of return to tolerance was described in self-antigen-specific CD8 + T cells following transient activation by homeostatic proliferation in lymphopenic hosts and was also ascribed to epigenetic imprinting (38). In transplantation, a T cell-restricted deficiency in IRF4 was recently reported to result in spontaneous donor-specific tolerance of cardiac allografts associated with impaired memory development and hyporesponsiveness of alloreactive CD4 + T cells, even if the animals received anti-PD1 and anti-CTLA-4 at the time of initial cardiac transplantation, which prevented graft acceptance (39,40). A similar phenomenon of return of tolerance may have been observed in kidney allograft recipient monkeys in which tolerance was induced by a regimen resulting in transient mixed chimerism, as injections of IL-2 resulted in rapid rejection of previously tolerated allografts, but cessation of IL-2 aborted the rejection process and restored kidney function (41).…”
Section: Discussionmentioning
confidence: 99%
“…Another setting of return to tolerance was described in self-antigen-specific CD8 + T cells following transient activation by homeostatic proliferation in lymphopenic hosts and was also ascribed to epigenetic imprinting (38). In transplantation, a T cell-restricted deficiency in IRF4 was recently reported to result in spontaneous donor-specific tolerance of cardiac allografts associated with impaired memory development and hyporesponsiveness of alloreactive CD4 + T cells, even if the animals received anti-PD1 and anti-CTLA-4 at the time of initial cardiac transplantation, which prevented graft acceptance (39,40). A similar phenomenon of return of tolerance may have been observed in kidney allograft recipient monkeys in which tolerance was induced by a regimen resulting in transient mixed chimerism, as injections of IL-2 resulted in rapid rejection of previously tolerated allografts, but cessation of IL-2 aborted the rejection process and restored kidney function (41).…”
Section: Discussionmentioning
confidence: 99%
“…They are essential for preventing autoimmunity and maintaining immune homeostasis and also play a key role in inducing T cell dysfunction that contributes to tumor immune escape, chronic persistent viral infection, and transplant tolerance 3 - 5 . Our recent study found that enhancing PD-1 expression in T cells by ablating the transcription factor, interferon regulatory factor 4 (IRF4), or inhibiting the MEK1/2 pathway led to T cell dysfunction and induced transplant tolerance in mice 6 , 7 . However, whether enhancing CTLA-4 expression of alloreactive T cells can prevent transplant rejection remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear whether T cell exhaustion naturally occurs in response to transplant 10 . We found that IRF4 deletion leads to transplant tolerance by inducing an exhaustion‐like phenotype of T cells, evident by their high PD‐1 expression and impaired cytokine production 11,12 . Miller et al 13 demonstrated that CD154 blockade plus donor‐specific transfusion, an experimental approach to transplant tolerance, also induces a PD‐1 hi phenotype of alloreactive T cells.…”
Section: Introductionmentioning
confidence: 76%
“…We demonstrated previously that transplant of Balb/c hearts (larger than the skin grafts) into B6 mice effectively activated both endogenous alloreactive T cells and the transferred TEa cells and did not induce T cell exhaustion/dysfunction. Indeed, we had to delete a transcription factor IRF4 to induce T cell dysfunction and transplant tolerance 11,12 . Interestingly, dramatically increasing graft size (eg, transplant of 2 kidneys plus 2 hearts in 1 recipient) or reducing alloreactive T cell frequency promotes the acceptance of MHC‐mismatched grafts 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation